Social work with disadvantaged and marginalised people - Parker, Jonathan, 1960-; Ashencaen Crabtree, Sara (Transforming Social Work Practice Series., 2018)
Split into three parts, this book considers what is meant by disadvantage and marginalisation, how this can come about and the impact this may have on lives, before unpicking the key knowledge and skills needed to practice effectively with individuals and groups.